Unravelled Chapters of Our Common Past / Unerschlossene Kapitel unserer gemeinsamen Vergangenheit - Harmatta, János; Csáky-Pallavicini, Roger (European Journal of Mental Health, 2008)
The European Journal of Mental Health launches a series of articles entitled ‘Unravelled Chapters of Our Common Past’ that primarily describes the history of operation of helping professions especially exposed to the effects of dictatorship (psychotherapy, charitable work, educational activity) in the era of state socialism. In order to eliminate the serious setback experienced in human disciplines we need to learn about the reasons and processes that led to the damages, after which we need to establish an extensive set of conditions, rephrase values, and ensure a long socialisation period, all of which support values taking root again. In order to do so resources need to be researched, professionals in the post-socialist countries need to cooperate and realise the new and extraordinary opportunities which lie before them on their common path. Research into the status of various disciplines in the era of the past dictatorship, and their description according to appropriate criteria in as many studies as possible may provide assistance in this, making our view of the past more articulate and differentiated. That the professionals who have firsthand knowledge of this age are still alive and active represents a special value. The more studies are received, the more refined our view of this period of the region will be.